2022
DOI: 10.3389/fcell.2022.992764
|View full text |Cite
|
Sign up to set email alerts
|

Role of adiponectin in osteoarthritis

Abstract: Osteoarthritis (OA) is a widespread and most common joint disease which leads to social cost increasing accompany with aging population. Surgery is often the final treatment option. The major progression of OA includes cartilage degradation caused by chondrocytes metabolism imbalance. So, the molecular mechanisms of action in chondrocytes may provide insights into treatment methods for OA. Adiponectin is an adipokine with many biological functions in the cell metabolism. Numerous studies have illustrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 150 publications
(161 reference statements)
0
5
0
Order By: Relevance
“…[4] Several studies have established a correlation between adipokines released by adipose tissue and OA. [5][6][7] Leptin, being one of the extensively studied adipokines, is believed to play a role in the development of OA. [8][9][10] A noteworthy study conducted by Griffin et al revealed that, contrary to adipose tissue, leptin plays a substantial role in the development of knee OA in female C57BL/6J mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Several studies have established a correlation between adipokines released by adipose tissue and OA. [5][6][7] Leptin, being one of the extensively studied adipokines, is believed to play a role in the development of OA. [8][9][10] A noteworthy study conducted by Griffin et al revealed that, contrary to adipose tissue, leptin plays a substantial role in the development of knee OA in female C57BL/6J mice.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Several studies have established a correlation between adipokines released by adipose tissue and OA. [ 5–7 ] Leptin, being one of the extensively studied adipokines, is believed to play a role in the development of OA. [ 8–10 ] A noteworthy study conducted by Griffin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, in patients with rheumatoid arthritis, there were no observed significant correlations between adiponectin levels and plasma levels of cytokines [34]. Moreover, another study reported that elevated ACRP-30 levels promote IL-8 and IL-6 secretion in rheumatoid arthritis patients, suggesting that augmented adiponectin levels promote the illness [35].…”
Section: Discussionmentioning
confidence: 95%
“…In addition to adipose tissue, adipokines are expressed in many other tissues. In recent years, the role of adipokines in the development and progression of OA has received increasing interest ( 12 , 13 ). At present, the known adipokines playing a role in the development and progression of OA include leptin, adiponectin, visfatin, resistin, progranulin, chemerin, lipocalin-2, vaspin, omentin-1 and nesfatin ( 14 , 15 ).…”
Section: The Role Of Adipokinesmentioning
confidence: 99%
“…Adiponectin has been described as a primarily anti-inflammatory adipokine ( 14 ). Nevertheless, adiponectin also demonstrates pro-inflammatory characteristics and suppression of chondrocyte metabolism in OA ( 12 , 26 , 34 ). Total adiponectin was significantly increased in women with advanced knee OA ( 35 ).…”
Section: The Role Of Adipokinesmentioning
confidence: 99%